2019
DOI: 10.2480/agrmet.d-18-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone on soil respiration rate of Siebold’s beech seedlings grown under different soil nutrient conditions

Abstract: Ozone O 3 is an air pollutant that negatively affect carbon budget in woody plants. In the present study, we aimed to clarify the effects of ozone on soil respiration rate of Siebold's beech seedlings Fagus crenata grown under different soil-nutrient conditions. Seedlings were grown under three levels of O 3 fumigation charcoal-filtered air or O 3 at 1.0 or 1.5 times ambient concentration in combination with three levels of nutrient supplies non-, low-or high-fertilised for two growing seasons. We determined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The exposure to O 3 significantly decreased ∆W in NF treatment, whereas there was no significant O 3 -induced reduction in ∆W in the LF and HF treatments ( Table 2). This result was in agree with the tendency in dry mass of the seedlings at the end of this experiment [26,42]. Similar results of lower O 3 susceptibility under higher nutrient condition were reported in the other studies on larch [30,43] and aspen [22] seedlings, although several studies demonstrated nitrogen supply-induced enhance of the susceptibility to O 3 in Siebold's beech [24] and Scots pine [44].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The exposure to O 3 significantly decreased ∆W in NF treatment, whereas there was no significant O 3 -induced reduction in ∆W in the LF and HF treatments ( Table 2). This result was in agree with the tendency in dry mass of the seedlings at the end of this experiment [26,42]. Similar results of lower O 3 susceptibility under higher nutrient condition were reported in the other studies on larch [30,43] and aspen [22] seedlings, although several studies demonstrated nitrogen supply-induced enhance of the susceptibility to O 3 in Siebold's beech [24] and Scots pine [44].…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in MRT by soil nutrient supply indicated a smaller increase in PND as compared to that of ∆N (Table 2). In this experiment, the dry mass ratio of fine roots to coarse roots was decreased by increased soil nutrient supply [42], indicating the possibility of lower N uptake efficiency. However, the contribution of lower nitrogen uptake efficiency was smaller compared to that of the greater soil N availability under the high fertilisation condition because we observed a clear increase in the ∆N of the seedlings with an increase in soil nutrient supply.…”
Section: Discussionmentioning
confidence: 66%
“…However, in mature Fagus species, different responses to elevated O 3 were also observed, such as stimulation of root growth [66,67] and no changes in carbon allocation into belowground tissues [68]. In addition, soil nutrient supply mitigated the negative impacts of O 3 on biomass allocation in F. crenata seedlings [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Trace gases such as ozone O 3 and nitrogen oxides NO x in the biosphere influence forest growth and carbon storage Ollinger et al, 2002 . O 3 results in a reduction of carbon fixation and biomass production Reich, 1987;Izuta et al, 1999;Watanabe et al, 2015Watanabe et al, , 2019Tani et al, 2017 , and atmospheric nitrogen deposition can result in increased growth of terrestrial ecosystems Vitousek and Howarth, 1991 . Biogenic volatile organic compounds BVOCs generate secondary organic aerosols that can affect the climate by affecting cloud formation Kanakidou et al, 2005 . Forest ecosystems are also an important sink and source of trace gases and particle matters in the atmosphere Slemr and Seiler, 1984;Yamaguchi et al, 2019 ; thus, observations of trace gas fluxes, such as O 3 Mikkenlsen et al, 2004;Gerosa et al, 2005;Matsuda et al, 2005 , NO x Rummel et al, 2002;Horii et al, 2004;Farmer et al, 2006, and BVOCs Guenther and Hills, 1998: Tani et al, 2002: Mochizuki et al, 2015 in forest ecosystems have been conducted.…”
Section: Introductionmentioning
confidence: 99%